Frequent non-response to histamine H2-receptor antagonists in cirrhotics. Issue 8 (August 1989) - Walker, S; Krishna, D R; Klotz, U; Bode, J C
Abstract : The effect of ranitidine 300 mg po given at 1800 h (famotidine 40 mg/cimetidine 800 mg) on the night time gastric pH was tested using longterm intragastric pH monitoring in 27 patients with and 32 patients without liver cirrhosis. A rise in the gastric pH above 4.0 for more than six hours between 1800 h and 0600 h was considered as sufficient effect (response) of the H2-receptor antagonists on gastric acidity. Among the patients with cirrhosis, there were significantly (p less than 0.005) more non-responders to ranitidine (16 of 27 patients) than in the control group (six of 32). When 13 of the 22 non-responders to ranitidine were subsequently treated with famotidine, only two showed a sufficient rise in their gastric pH. Of the 11 patients not responding to both H2-receptor antagonists, 10 were finally treated with cimetidine and eight did not respond. Plasma levels of all three drugs measured two and four hours after oral administration were not significantly different between cirrhotic and noncirrhotic patients as well as between responders and non-responders. In addition, in all patients plasma levels were far above the corresponding IC50 values. Therefore, differences in the absorption and plasma levels of these drugs cannot account for the frequent non-response in cirrhotics.